Tuning the conductance of a molecular wire by the interplay of donor and acceptor units. Issue 36 (5th September 2018) - Skidin, Dmitry; Erdmann, Tim; Nikipar, Seddigheh; Eisenhut, Frank; Krüger, Justus; Günther, Florian; Gemming, Sibylle; Kiriy, Anton; Voit, Brigitte; Ryndyk, Dmitry A.; Joachim, Christian; Moresco, Francesca; et al.
Abstract : Conductance of optimized donor–acceptor–donor molecular wires obtained by on-surface synthesis. Abstract : We investigate the conductance of optimized donor–acceptor–donor molecular wires obtained by on-surface synthesis on the Au(111) surface. A careful balance between acceptors and donors is achieved using a diketopyrrolopyrrole acceptor and two thiophene donors per unit along the wire. Scanning tunneling microscopy imaging, spectroscopy, and conductance measurements done by pulling a single molecular wire at one end are presented. We show that the conductance of the obtained wires is among the highest reported so far in a tunneling transport regime, with an inverse decay length of 0.17 Å −1 . Using complex band structure calculations, different donor and acceptor groups are discussed, showing how a balanced combination of donor and acceptor units along the wire can further minimize the decay of the tunneling current with length.